1999
DOI: 10.1177/014920639902500501
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Blame Attributions and Offender Likableness on Forgiveness and Revenge in the Workplace

Abstract: This study proposes and tests a model that applies the concept of restorative justice to the enactment of revenge and forgiveness in organizations. The model draws from theories of cognitive attribution and consistency, as well as more recent theories of revenge in organizations, to describe the process by which a personal offense triggers revenge and forgiveness cognitions and behavior. Attributions of blame were predicted to directly influence the contemplation of revenge and forgiveness strategies. In turn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
228
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(237 citation statements)
references
References 60 publications
8
228
0
1
Order By: Relevance
“…A number of items also address the victim's perception of the transgression (magnitude of offense, other possible explanations, blame attributions, mitigating circumstances, communication about the incident) and reinforce studies that have found a significant association between these type of victim perceptions and degree of forgiving response (e.g., Bradfield & Aquino, 1999;Fincham, 2000;Worthington et al, 2000). …”
Section: Telling the Person It's Okay What They Did)mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of items also address the victim's perception of the transgression (magnitude of offense, other possible explanations, blame attributions, mitigating circumstances, communication about the incident) and reinforce studies that have found a significant association between these type of victim perceptions and degree of forgiving response (e.g., Bradfield & Aquino, 1999;Fincham, 2000;Worthington et al, 2000). …”
Section: Telling the Person It's Okay What They Did)mentioning
confidence: 99%
“…Research on forgiveness is growing rapidly, including the roles played by situational factors (McCullough, Fincham, & Tsang, 2003;Takaku, 2001), intrapersonal factors and individual differences (Bradfield & Aquino, 1999;Brown, 2003;Konstam, Chernoff, & Deveney, 2001) and dyadic relational factors (Fincham & Beach, 2002;Finkel, Rusbult, Kumashiro, & Hannon, 2002;Friesen et al, 2005). However, as mentioned earlier, there has been relatively little interest in a possible consensual lay representation of forgiveness, and only a handful of studies have examined forgiveness from a lay perspective.…”
Section: Lay Perspectives Of Forgivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Commitment to a relationship also strengthens over time (e.g., McCullough et al, 1998;Bradfield & Aquino, 1999;Fincham, 2000;Orth, 2004;Kidder, 2007). Commitment, in this sense, indicates concern for the interests of the partner and the relationship (Finkel et al 2002, Rusbult et al 1991, Van Lange et al 1997).…”
Section: Positive Relationships and Ruminationmentioning
confidence: 99%
“…For example, some personality traits have been shown to correlate positively with forgiveness, such as agreeableness (e.g., Ashton, Paunonen, Helmes, & Jackson, 1998;McCullough & Hoyt, 2002) and emotional stability (e.g., Ashton et al, 1998;Berry, Worthington, Parrott, O'Connor, & Wade, 2001). When individuals forgive, they tend to make generous attributions about and evaluations of the transgressor and the transgression (e.g., Bradfield & Aquino, 1999;Shapiro, 1991). Other research has shown that forgiving responses have positive outcomes for victims, including reduction of negative emotions, better physical health (Witvliet, Ludwig, & Vander Laan, 2001), and improved mental health (Burnette, Davis, Green, Worthington, & Bradfield, 2009;Coyle & Enright, 1997;Freedman & Enright, 1996).…”
Section: Theory and Research On Forgivenessmentioning
confidence: 99%